2018
DOI: 10.1111/acel.12765
|View full text |Cite
|
Sign up to set email alerts
|

Metformin alleviates human cellular aging by upregulating the endoplasmic reticulum glutathione peroxidase 7

Abstract: SummaryMetformin, an FDA‐approved antidiabetic drug, has been shown to elongate lifespan in animal models. Nevertheless, the effects of metformin on human cells remain unclear. Here, we show that low‐dose metformin treatment extends the lifespan of human diploid fibroblasts and mesenchymal stem cells. We report that a low dose of metformin upregulates the endoplasmic reticulum‐localized glutathione peroxidase 7 (GPx7). GP×7 expression levels are decreased in senescent human cells, and GPx7 depletion results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 50 publications
1
101
0
2
Order By: Relevance
“…GPx7 is responsible for direct elimination of the H 2 O 2 produced by Ero1α [30] . We have previously elucidated that GPx7 can be induced in human fibroblasts by NRF2, the master transcription factor responsible for cellular antioxidant response [32] . Here, we observed that the protein expression of NRF2 and GPx7 in HUVECs was elevated time-dependently after Hcy treatment ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GPx7 is responsible for direct elimination of the H 2 O 2 produced by Ero1α [30] . We have previously elucidated that GPx7 can be induced in human fibroblasts by NRF2, the master transcription factor responsible for cellular antioxidant response [32] . Here, we observed that the protein expression of NRF2 and GPx7 in HUVECs was elevated time-dependently after Hcy treatment ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the Ero1α/GPx7/PDI triad couples H 2 O 2 elimination and disulfide generation to ensure efficient and safe oxidative protein folding [30] . Interestingly, deficiency of GPx7 is associated with increased carcinogenesis and shortened lifespan [31] , [32] . Nevertheless, whether GPx7 plays a role and the relationship between GPx7 and Ero1α in Hcy-induced ER oxidative stress are still open questions.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently established a platform of Werner syndrome (WS) and Hutchinson-Gilford progeria syndrome (HGPS) hMSCs for studying premature and physiological aging (Fang et al, 2018 ; Kubben et al, 2016 ; Li et al, 2016b ; Wu et al, 2018 ; Yang et al, 2017 ; Zhang et al, 2015 ). Here, we took advantage of this platform and screened for natural product compounds capable of alleviating premature senescence (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in our study decreased ROS levels may also contribute to the restoration of heterochromatin architecture. In addition, we have recently demonstrated that, the premature aging phenotypes in HGPS hMSCs partially attributes to the repression of NRF2-mediated anti-oxidative response, whereas the reactivation of NRF2 reverses the nuclear defects in HGPS cells and restores their in vivo viability in mice (Fang et al, 2018 ; Kubben et al, 2016 ). Interestingly, Que is reported as an activator of NRF2-mediated anti-oxidative pathway (Bahar et al, 2017 ; Dai et al, 2018 ; Gao et al, 2018 ; Kim et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…IgG-FITC, IgG-PE, and IgG-APC were used as isotype controls. The differentiation abilities of MSCs to adipocytes, osteoblasts and chondrocytes were assessed by oil red O, Von Kossa and Toluidine blue staining, respectively (Duan et al, 2015 ; Fang et al, 2018 ; Yang et al, 2017 ; Zhang et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%